Processing of Red Dahlia Tubers in Produce Inulin Extract and Material Proximate Testing - Sunarti Sunarti; Chrismis Novalinda Ginting; Sahna Ferdinand Ginting (Future Science)
Dahlia tubers from Berastagi, North Sumatra, are plants that contain carbohydrates and contain high levels of inulin. Inulin is very good as a dietary fiber and has other physiological functions such as lowering blood sugar and blood fat, anticancer, regulating intestinal microbial flora, increasing absorption of minerals and vitamins. Currently, the utilization of dahlia tubers is not optimal in the community and is considered as agricultural waste, therefore it is necessary to manage dahlia tubers in producing inulin extract and study the proximate material, considering that previous studies still obtained varying results. This study aimed to obtain inulin extract and its yield value and to measure the proximate material of red dahlia tuber. The extraction method used is based on the solubility of inulin in water at a temperature of 800 C. And precipitation are carried out with 70% ethanol. Proximate examination of the material consisted of water content using the heating method, ash content using the gravimetric method, fat and crude fiber content using the Soxhlet method, determination of protein content using the Macro Kjedhal method, and carbohydrate content using the proximate method using the carbohydrate percentage formula. The results obtained were 48,25% Inulin Flour yield, the proximate results obtained 80,8% water content, 0,36% ash content, 0,33% total fat content, 1,29% crude fiber content, protein content 1,15%, Carbohydrate content 14.6%. From this study, it can be concluded that dahlia tubers contain high carbohydrates and low-fat content, have crude fiber and protein that can be used as low-calorie foodstuffs.